Meloeiro cultivado em solo arenoso em resposta a doses de nitrogênio e potássio - Vale, Amsterdam Armênio de Medeiros (Universidade Federal Rural do Semi-Árido, 2017)
Fertigation is one of the main technologies used to increase crop productivity and profitability, since it allows the supply of nutrients according to the nutritional needs of the plants. What is observed in the researches is that its management through nutrient absorption curves and fertilizer application recommendations has not always presented the expected results, besides, in some practical cases, economic and environmental losses are observed. In this sense, fertirrigation through the management of applied nitrogen and potassium concentrations has presented promising responses to crops, fertilization control and soil salinity, but there is still little technical and scientific information for the producing class. The objective of the research was to improve the technique of fertirrigation management by controlling the nitrogen and potassium doses applied in sandy soil cultivated with melon so as to find minimum doses adequate for melon development and to contribute to the reduction of costs production and contamination of the environment. The research was carried out in a greenhouse in the experimental design of randomized blocks with four replicates and 13 treatments arranged in 156 vessels. The treatments were composed of different percentages of N and K (0-0, 0-100, 0-200, 50-50, 50-150, 100-0, 100-100, 100-200, 150-50,150 -150, 200-0, 200-100, 200-200) relative to a standard dose of N and K (3.3 and 10.6 g pot-1), respectively. The culture used was Gaul melon with plants conducted under drip fertirrigation and increasing doses of nitrogen and potassium were applied in the treatments. The characteristics evaluated in the culture were: vegetative development, nutritional status, fruit production and quality, soil content, nitrate and potassium ion content, electrical conductivity and soil solution pH, as well as changes in fertility. Analyzes of variance and regression were performed, observing that N accumulation decreases with increasing K concentration in the soil solution; That the quality characteristics of the fruits had better performance, in the majority, in the initial dose of N and K; That K was the nutrient most absorbed by the plant presenting the best results of vegetative development at the maximum dose of this nutrient (24.35 g pot-1); That the applied fertirrigation interacted with the nutrients of the soil facilitating the accumulation of P, K, Ca and Na
Meloeiro cultivated in sandy soil in response to nitrogen and potassium doses
Keywords: Cucumis melo L; Controle de íons; Fertirrigação; Cultivo protegido; Cucumis melo L; Ion control; Fertigation; Protected cultivation; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO